A molecular assembly phase transition and kinetic proofreading modulate Ras activation by SOS - Huang, William Y. C. (2021)
The guanine nucleotide exchange factor (GEF) Son of Sevenless (SOS) is a key Ras activator that is autoinhibited in the cytosol and activates upon membrane recruitment. Autoinhibition release involves structural rearrangements of the protein at the membrane and thus introduces a delay between initial recruitment and activation. In this study, we designed a single-molecule assay to resolve the time between initial receptor-mediated membrane recruitment and the initiation of GEF activity of individual SOS molecules on microarrays of Ras-functionalized supported membranes. The rise-and-fall shape of the measured SOS activation time distribution and the long mean time scale to activation (~50 seconds) establish a basis for kinetic proofreading in the receptor-mediated activation of Ras. We further demonstrate that this kinetic proofreading is modulated by the LAT (linker for activation of T cells)–Grb2–SOS phosphotyrosine-driven phase transition at the membrane.